Pavement Design Comparative Analysis Using Bina Marga Design Method (Pt T-01-2002-B) And Pavement Design Manual (No.04/Se/Db/2017) (Case Study: Trisakti Port - Liang Anggang): Analisa Perbandingan Antara Desain Pavement Bina Marga (Pt T-01-2002-B) dengan Desain Pavement Manual (No.04/Se/Db/2017) dengan Studi Kasus : Pelabuhan Trisakti – Liang Anggang - Utami Sylvia Lestari; Nurhafni Karina Resentia (POROS TEKNIK, 2017)
Traffic load repetition is the main variable in flexible pavement layers design. In addition, a soil bearing capacity factor is also required for determining the thickness of the flexible pavement layer so that the pavement had been designed will be in good perfomance during the that period. The determination of thickness layers using the 2002 method (Pt T-01-2002 B) is based on the traffic load during the design period and subgrade resilient modulus value. Meanwhile the 2017 method (Pavement design manual No. 04/SE/Db/2017), layers thickness was determined based on traffic load and CBR subgrade value. Based on the calculation using both methods, the pavement layers thickness with the pavement design manual 2017 method is more thick than 2002 method. While the ESAL calculation using both methods, the 2002 method value is more larger than the pavement design manual 2017 method.